Proposal of life cycle-based environmental performance indicators for decision-making in construction. - Silva, Fernanda Belizario (2022)
Humanity must drastically reduce the impacts caused on the environment, especially global warming, and the construction sector contributes significantly to many environmental impacts. Therefore, improving the environmental performance throughout the life cycle of buildings is essential, especially because there is still much to build. Despite this, most decisions in this sector do not consider environmental criteria. This work aims to propose a set of indicators to measure the environmental performance throughout the life cycle of buildings in a practical and accessible way so that these indicators can be used for decision-making. To this end, the characteristics that can increase the probability of using environmental performance indicators for decision making are identified: indicators must be focused on priority environmental aspects, reliable, comparable, and easy to measure and understand. Life Cycle Assessment (LCA) is the most recommended method for assessing the environmental performance of construction. Therefore, a cradle-to-grave LCA study of a typical Brazilian building is performed to understand the meaning of each impact result. It is concluded that LCA indicators cover too many impact categories, some caused by processes that the construction sector can hardly influence. Also, LCA indicators are difficult to measure and understand. Thus, a simplification of LCA is proposed, resulting in five indicators to assess the environmental performance over the construction life cycle: material demand, energy demand, water demand, land occupation and CO2 emission. These indicators present low correlation among themselves, assess priority environmental aspects that the construction sector can influence, and can be easily measured and understood. This proposal is expected to increase the use of life-cycle based environmental performance indicators to guide decisions and reduce the environmental impacts caused by the construction sector.